Evaluation of oral wetness using an improved moisture‐checking device for the diagnosis of dry mouth. Issue 2 (6th January 2017) - Fukushima, Yosuke; Yoda, Tetsuya; Araki, Ryuichiro; Sakai, Takayoshi; Toya, Shuji; Ito, Kayoko; Funayama, Saori; Enoki, Yuichiro; Sato, Tsuyoshi
Abstract: Purpose: In 2013, we reported the results of a third‐generation oral moisture‐checking device in a multicentre clinical study involving patients with dry mouth and healthy volunteers. Subsequently, several improvements have been made to the third‐generation device, and a fourth‐generation device is now commercially available. This study aimed to confirm the usefulness of this improved fourth‐generation device in the diagnosis of dry mouth and to assess the physiological wetness of lingual mucosa by using this device. Materials and Method: This multicentre study comprised subjects with dry mouth (dry mouth group) and those without dry mouth (healthy group). Results: In this study, the degree of moisture was considerably different between the two groups. Receiver operating characteristic analysis revealed an area under the curve value of 0.831. Sensitivity and specificity values were close to 80% in cases where the degree of moisture ≥29.6 was defined as normal, ≤27.9 was defined as dry mouth, and 28.0–29.5 was defined as borderline dry mouth. Conclusions: These results suggest that the improved fourth‐generation moisture‐checking device can be used for the diagnosis of oral dryness.